The Impact: Employer Brand, Corporate Social Responsibility, and Organizational Reputation in Job Application Intentions - Fazah Zikri Soleha; Aryana Satrya (Eduvest - Journal of Universal Studies, 2024)
Creating a competitive advantage is essential for companies as it serves as leverage to attract competent job seekers needed for the sustainability of the business. This research aims to examine the direct role of employer brand attractiveness and corporate social responsibility as dependent variables in influencing intention to apply, as well as the indirect influence of organizational reputation mediating the relationship between employer brand attractiveness and corporate social responsibility on intention to apply as independent variables. Data were collected through a self-administered questionnaire distributed to a total of 315 respondents. The respondents were final-year students and fresh graduates who had not yet entered the workforce and were part of Generation Z in Indonesia. The questionnaire utilized a 7-point Likert scale, and Structural Equation Modeling (SEM) was employed to analyze and elucidate the relationships among the variables used in this study. The results indicate that employer brand attractiveness and corporate social responsibility significantly and positively influence intention to apply. Meanwhile, organizational reputation influences the relationship between employer brand attractiveness and corporate social responsibility with the intention to apply through positive mediation. Based on this research, companies can learn how to shape a reputation that serves as a competitive advantage in enhancing employer brand attractiveness and corporate social responsibility among Generation Z as a potential new workforce entering the job market.